2011
DOI: 10.19030/jber.v7i2.2259
|View full text |Cite
|
Sign up to set email alerts
|

Demographics In Civil Trials: Biases And Implications

Abstract: This paper investigates the implications of the demographics of jury members and its influence on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…12 Another study found that a victim's credibility, presence of injury, use of force/weapon and corroborating evidence affected police and court outcomes. 13 Although prosecutors and jurors look for corroborative evidence to support a complainant's word, most sexual assault cases do not involve injury to the complainant, use of a weapon, eyewitnesses or forensic evidence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Another study found that a victim's credibility, presence of injury, use of force/weapon and corroborating evidence affected police and court outcomes. 13 Although prosecutors and jurors look for corroborative evidence to support a complainant's word, most sexual assault cases do not involve injury to the complainant, use of a weapon, eyewitnesses or forensic evidence.…”
mentioning
confidence: 99%
“…11 The focus of prosecutorial decisions has been partly empirically validated in a study which found that criminal proceedings were more likely to be instigated if there was less than a 10-year gap between the offence and report to the police, 'if the offence involved some aggravating factor' and if the victim was older than 10 years and 'could be regarded as more credible'. 12 Another study found that a victim's credibility, presence of injury, use of force/weapon and corroborating evidence affected police and court outcomes. 13 Although prosecutors and jurors look for corroborative evidence to support a complainant's word, most sexual assault cases do not involve injury to the complainant, use of a weapon, eyewitnesses or forensic evidence.…”
mentioning
confidence: 99%